The Effect of Income from Part-Time Employment and Investment Motivation on Sharia Investment Interest - Nanda Ardi Tama; Soemitra, Andri; Harahap, Muhammad Ikhsan (Islamic Economics and finance in Focus, 2026)
The increasing growth of sharia investment in Indonesia has encouraged greater participation among university students, making it important to identify the factors influencing their interest in sharia investment. This study aims to analyze the effect of income from part-time employment and investment motivation on students’ interest in sharia investment. This study employed a quantitative approach using a survey method by distributing questionnaires to 98 respondents selected through probability sampling. The data were analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with SmartPLS 4. The results indicate that income from part-time employment has a positive and significant effect on students’ interest in sharia investment (t = 3.557, p < 0.001). Investment motivation also has a positive and significant effect (t = 6.946, p < 0.001) and exerts a stronger influence than income. Furthermore, both variables explain 55.9% of the variance in students’ interest in sharia investment (Adjusted R² = 0.559). These findings imply that universities should strengthen sharia investment education and encourage students to improve their financial capability and investment motivation to enhance participation in sharia investment.